Management of pulp stone in molar teeth: literature review: Penanganan pulp stone pada gigi molar: kajian pustaka - Juni Jekti Nugroho; Sri Wahyuni (Makassar Dental Journal, 2019)
Introduction:Pulp stone is a calcification found in the pulp chamber or root canal of a tooth.Causative factors of pulp stone formation are age, caries process, restoration, long-standing pulp irritation, interference of pulp circulation, tooth movement in orthodontic treatment, and trauma. Clinically the pulp stone is irregular, hard and looks like a crystal. On radiographic examination it appears radiopaque. The effective way to remove pulp stone is using ultrasonic devices. The presence of pulp stone in the pulp chamber or root canal can located close to orifice so that it becomes a challenge for operators in endodontic treatment. One factor in the success of endodontic treatment is hermetic obturation. But this procedure is difficult to achieve because the pulp chamber is calcified. Aim: To determine the etiology, prevalence, identify clinically and radiographically, and how to remove pulp stone. Conclusion: Pulp stone is more common in molar teeth. Removing pulp stone using ultrasonic is more effective than using bur.